Understanding Post-Pandemic Inflation Fluctuations: The Commodity Cost Channel - Gert Peersman (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper employs a joint SVAR-IV model for the United States and the euro area to estimate the pass-through of energy and food commodity cost shocks to inflation. Exogenous commodity cost shocks — such as those triggered by the Russian invasion of Ukraine — had only a modest impact on inflation during the post-pandemic period. However, counterfactual analyses based on the pass-through estimates indicate that overall commodity cost fluctuations — including their endogenous responses to macroeconomic conditions — can almost fully account for the rise and subsequent decline of energy, food, and core CPI inflation over this period. These findings highlight that commodity costs constitute a key transmission channel through which macroeconomic developments affect inflation. Estimates of a standard Phillips Curve specification, including its slope, are shown to be severely biased when this channel is ignored.
Keywords: E31; Q11; Q43; 330; commodity costs; post-pandemic inflation; Phillips curve